Історія інтродукції видів роду Berberis L. в Україні та перспективи використання їх в озелененні - Sushinska, N.I. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2006)
On the basis of the literary sourses the history of introduction and modern condition of collections of Berberis genus in botanical gardens and dendrological parks of Ukraine are stated. There are 106 kinds of Berberis are revealed in traditional collections, from which 10 hybrids and 21 garden forms. However for wide use and introduction in Ukraine 19 kinds are recommended only.